Look-alikes, Jr. - Steiner, Joan (Joan Catherine); Lindley, Thomas (Boston : Little, Brown & Co., 1999)
Simple verses challenge readers to identify the everyday objects used to construct eleven three-dimensional scenes, including a house, kitchen, bedroom, school bus, train, farm, and rocket.
NP
Accelerated Reader AR
Keywords: Picture puzzles -- Juvenile literature; Picture puzzles